Proceedings Twentieth International Symposium on Logical and Semantic Frameworks with Applications - Barbosa, Haniel; Ringeissen, Christophe (Electronic proceedings in theoretical computer science, 2025)
This volume contains the proceedings of the 20th Workshop on Logical and Semantic Frameworks with Applications (LSFA 2025), which was held in Brasilia, the capital of Brazil, from October 7 to October 8, 2025. The aim of the LSFA series of workshops is bringing together theoreticians and practitioners to promote new techniques and results, from the theoretical side, and feedback on the implementation and use of such techniques and results, from the practical side. LSFA includes areas such as proof and type theory, equational deduction and rewriting systems, automated reasoning and concurrency theory.